Agricultural management strategies in a changing economy - Popescu, Gabriel; Jean-Vasile, Anil (Advances in finance, accounting, and economics (AFAE) book series., 2015)
"This book brings together emergent research and best practices in the area of agricultural management, policy, and structures, highlighting theoretical concepts and empirical research"--